Recent advancements in supercapacitor technology. (October 2018) - Raza, Waseem; Ali, Faizan; Raza, Nadeem; Luo, Yiwei; Kim, Ki-Hyun; Yang, Jianhua; Kumar, Sandeep; Mehmood, Andleeb; Kwon, Eilhann E.
Abstract: Supercapacitors (SCs) are attracting considerable research interest as high-performance energy storage devices that can contribute to the rapid growth of low-power electronics (e.g., wearable, portable electronic devices) and high-power military applications (e.g., guided missile techniques and highly sensitive naval warheads). The performance of SCs can be assessed in terms of the electrochemical properties determined through a combination between the electrode and the electrolyte materials. Likewise, the charge storage capacities of SCs can be affected significantly by selection of such materials (e.g., via surface redox mechanisms). Enormous efforts have thus been put to make them more competitive with existing options for energy storage such as rechargeable batteries. This article reviews recent advances in SC technology with respect to charge storage mechanisms, electrode materials, electrolytes (e.g., particularly paper/fiber-like 3D porous structures), and their practical applications. The challenges and opportunities associated with the commercialization of SCs are also discussed. Graphical abstract: fx1 Highlights: There has been great demand for a reliable technical platform for electrochemical storage. SCs are highly attractive option due to their fast storage capability and enhanced cyclic stability. This review covers the charge storage mechanisms of SCs along with comparison of selected SCs. We also discuss the technical challenges for developing SCs with high enough energy density.